In situ ionic liquid dispersive liquid–liquid microextraction combined with ultra high performance liquid chromatography for determination of neonicotinoid insecticides in honey samples. Issue 10 (2nd April 2019) - Yang, Chong; Ran, Lu; Xu, Meilin; Ren, Dabing; Yi, Lunzhao
Abstract: An efficient in situ ionic liquid dispersive liquid–liquid microextraction followed by ultra‐performance liquid chromatography was developed to determine four neonicotinoid insecticides in wild and commercial honey samples. In this method, a hydrophobic ionic liquid 1‐butyl‐3‐methylimidazolium hexafluorophosphate, formed by in situ reaction between potassium hexafluorophosphate and 1‐butyl‐3‐methylimidazolium bromide in sample solution, was used as the extraction solvent. In comparison with the traditional dispersive liquid–liquid microextraction method, the developed method required no dispersive solvent. To achieve high extraction efficiency and enrichment factor, the effects of various experimental parameters were studied in detail. Under the optimized conditions, the limits of detection and quantification were in the ranges of 0.30–0.62 and 1.20–2.50 μg/L, respectively. The method showed high enrichment factors (74–115) with the recoveries between 81.0 and 103.4%. The proposed method was finally applied to different wild and commercial honey samples.